Pros and cons of using a standard protocol to test germination of alpine species - Vera Margreiter; Konrad Pagitz; Christian Berg; Patrick Schwager; Brigitta Erschbamer (Plant Ecology, 2020)
Storing seeds in seed banks is an effective way to preserve plant diversity and conserve species. An essential step towards a valuable conservation is the validation of germination. This study presents a germination screening of seeds from 255 species of the European Eastern Alps, which were to be stored at the Millennium Seed Bank (Kew, UK). The final germination percentage (FGP) was determined using a standard protocol in the laboratory. Species were classified according to species rarity, plant community, occurrence at elevation belts, bedrock types, as well as CSR strategies, and further, seed mass was examined. We could not find statistically significant differences of FGP within these classes, but 74.9% of all tested species germinated using the standard protocol, and half of them had FGP ≥ 20.1–100%. A treatment with gibberellic acid enhanced the germination in half of the species to which this treatment was applied. Common families in alpine regions, i.e. Asteraceae, Poaceae and Saxifragaceae were highlighted in terms of their germination behaviour. The results provide an evaluation of the application of standard protocols to a broad Alpine species pool on the one hand, and on the other hand, provide ecological insights of the species tested. Germination is not only one of the most important events of the reproductive cycle of plants but could also be a key feature in species' responses to changing environmental conditions.